Movement and distribution of particles in the tank of jet and agitation combined flotation machine - Tao WANG; Wei ZHOU; Zilei WANG; Shujie WANG; Lingling WANG; Liang LI (Meitan xuebao, 2024)
In order to explore the movement and distribution of particles in the tank of jet and agitation co-flotation machine, a geometric model of the tank of jet and agitation co-flotation machine was established. The COMSOL software was used to simulate the flow field distribution and particle movement in the flotation tank under impeller agitation, and a test system of jet and agitation co-flotation device was set up to test the particle dispersion effect. The results showed that some particles pass through the gap between the impeller blades and spiral downward under the action of flow field, the other part of the particles are thrown out by the blade and move helically around and up under the coupling effect of the blade and the flow field. The trajectory curves of all particles were drawn to explore the particle movement and distribution law during the operation of the flotation machine. It was found that the trajectory curves of particles at the bottom of the flotation cell, around the wall and at the corner of the tank have a high coincidence degree, which indicates that the probability of particles moving there is large. The coincidence degree of particle motion trajectories in the upper part of the flotation tank and the area between the wall and the impeller is small, and the probability of particle movement there is low, and only a few particles are distributed there. The uniformity of particle distribution does not increase with the increase of impeller stirring speed, but there is an optimal impeller working parameter. The results of simulation and test showed that the jet and agitation co-flotation machine has better particle dispersion performance under the condition of impeller speed of 6.25 r/s. The particle dispersion is affected by the shape and internal structure of the tank. Adding baffle or using column flotation cell can effectively promote the uniform distribution of particles. The study of the movement and distribution of particles in the tank is beneficial to optimize the structure of the jet and agitation co-flotation machine and improve its flotation efficiency.